Depression, anxiety and self-esteem in adolescent girls with polycystic ovary syndrome: a systematic review and meta-analysis - Li, Yuxin; Zhang, Jiayu; Zheng, Xuanling; Lu, Wenjing; Guo, Jinru; Chen, Fuhong; Liu, Changqin (Frontiers in Endocrinology, 2024)
Objective Studies have shown the adverse psychological impact of polycystic ovary syndrome (PCOS), but the state of mental health in adolescents with PCOS remains unclear. Thus, we performed a systematic review and meta-analysis to investigate the prevalence and severity of depression and anxiety, as well as potential effects on self-esteem and quality of life (QoL) in this specific population. Methods We systematically searched four electronic databases: PubMed, Embase, Web of Science, and the Cochrane Reviews database for articles published until 25/8/2024. We considered observational studies in which the subjects were adolescent girls with PCOS who had reported symptoms including anxiety, depression, self-esteem, and QoL. The Review Manager version 5.4 was used to analyze the available data extracted. We used the Newcastle-Ottawa Quality Assessment Scale (NOS) to evaluate the quality of selected studies. A funnel plot was utilized to assess the risk of literature bias, and a forest plot was used to represent the combined outcomes. This systematic review was previously registered in PROSPERO with the registration number CRD42022382036. Results We included 11 studies in the systematic review and conducted meta-analyses on 10 of them. Adolescents with PCOS reported a higher risk of depression (OR = 2.21, 95% CI: 1.23 to 4.00, p = 0.008) and a higher level of depression scores (SMD = 0.43, 95% CI: 0.16 to 0.71, p = 0.002) than controls. There were no significant differences in anxiety (OR = 1.90, 95% CI: 0.52 to 6.96, p = 0.33; SMD = 0.19, 95% CI: -0.21 to 0.59, p = 0.36), self-esteem (SMD = -0.17, 95% CI: -0.85 to 0.52, p = 0.64), and QoL (SMD = -0.15, 95% CI: -0.42 to 0.11, p = 0.26) between the two groups. Conclusions Our research indicated that adolescents with PCOS experienced more severe depressive symptoms than those without PCOS. This highlights the importance of evaluation and early treatment of mental health in PCOS. More clinicians should pay attention to the mental health of adolescent girls with PCOS through this study. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022382036.